2018
DOI: 10.1086/696143
|View full text |Cite
|
Sign up to set email alerts
|

Taxing Childcare: Effects on Childcare Choices, Family Labor Supply, and Children

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 68 publications
(52 reference statements)
1
22
0
1
Order By: Relevance
“…8 See, for instance, Carneiro et al (2015); Elango et al (2016); Gathmann and Sass (2018); Havnes and Mogstad (2011). above and provides mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…8 See, for instance, Carneiro et al (2015); Elango et al (2016); Gathmann and Sass (2018); Havnes and Mogstad (2011). above and provides mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Givord & Marbot (2015) estimate that maternal labour force participation increased by around 1 percentage point in the short-term. Gathmann & Sass (2018) show that a relative increase in day care costsresulting from a subsidy for home-based care in one federal statereduces day care attendance by 8 percentage points, with no effects on maternal labour supply. Busse & Gathmann (2018) provide first evidence on effects of day care fee abolitions for Germany.…”
Section: Introductionmentioning
confidence: 94%
“…Failure to complete secondary school makes it almost impossible to progress to higher education and even, purely for financial and practical reasons, to resume studying, especially at upper secondary level. Various studies have shown what a negative net effect teenage motherhood has on women's participation in education (Luong, 2008[9]; Fletcher and Wolfe, 2009 [10]). 12 Whether pregnancy or the birth of a child is the cause for the interruption of studies or, conversely, whether there are pre-existing socio-economic conditions that increase the probability both of early parenthood and of dropping out of school is an important research question, but one that cannot be answered with PIAAC data.…”
Section: Teenage Parentsmentioning
confidence: 99%